New dipyranocoumarin from the leaves of calophyllum apetalum willd - Joshi, Swati P.; Kulkarni, Smita R.; Phalgune, Usha D.; Puranik, Vedavati G. (Natural Product Research, 2013)
A new dipyranocoumarin, -hydroxytomentolide A (1) was isolated from the leaves of Calophyllum apetalum together with the known compounds friedelin (2), apetalactone (3), inophyllum C (4) and canophyllol (5). The structure of the new compound was established by spectroscopic studies which include H-1 NMR, C-13 NMR, NOESY, HetCOSY, COLOC experiments and single crystal X-ray diffraction analysis.
Keywords: -hydroxytomentolide A; Calophyllum apetalum; dipyranocoumarins; Guttiferae; Triterpenoids